2022
DOI: 10.1364/optcon.457365
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural network-based retrieval of Raman signals from CARS spectra

Abstract: We report the studies on the automatic extraction of the Raman signal from coherent anti-Stokes Raman scattering (CARS) spectra by using a convolutional neural network (CNN) model. The model architecture is adapted from literature and retrained with synthetic and semi-synthetic data. The synthesized CARS spectra better approximate the experimental CARS spectra. The retrained model accurately predicts spectral lines throughout the spectral range, even with minute intensities, which demonstrates the potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“… 35 In our recent work, we have also demonstrated that the training with semi-synthetic data in addition to the synthetic data improves the DL model performance. 36 The SpecNet model performance was found to be poor when compared with our previous work 36 and VECTOR model, 35 where it could not able to extract the spectral lines with minimal intensities. More importantly, they have not evaluated the model accuracy quantitatively.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“… 35 In our recent work, we have also demonstrated that the training with semi-synthetic data in addition to the synthetic data improves the DL model performance. 36 The SpecNet model performance was found to be poor when compared with our previous work 36 and VECTOR model, 35 where it could not able to extract the spectral lines with minimal intensities. More importantly, they have not evaluated the model accuracy quantitatively.…”
Section: Introductionmentioning
confidence: 76%
“…A similar observation was noticed in our previous work. 36 Further, this inefficient extraction of the Raman spectrum has given an SE of ∼0.29 at the peak centre and led to the lowest PCC in the entire test set, i.e. , ∼0.11.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations